2018
DOI: 10.1038/s41598-018-21497-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced release of acid sphingomyelinase-enriched exosomes generates a lipidomics signature in CSF of Multiple Sclerosis patients

Abstract: Multiple Sclerosis (MuS) is a complex multifactorial neuropathology, resulting in heterogeneous clinical presentation. A very active MuS research field concerns the discovery of biomarkers helpful to make an early and definite diagnosis. The sphingomyelin pathway has emerged as a molecular mechanism involved in MuS, since high levels of ceramides in cerebrospinal fluid (CSF) were related to axonal damage and neuronal dysfunction. Ceramides are the hydrolysis products of sphingomyelins through a reaction cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 37 publications
2
101
0
Order By: Relevance
“…Recent studies indicate that myeloid cells can release EVs/MP that spread inflammatory signals both in vitro and in vivo to alter neuronal functions (Harrison-Brown et al, 2016;Nigro et al, 2016;Beneventano et al, 2017;Kumar et al, 2017). Importantly, EV levels are significantly increased following TBI in humans and animal models, as well as in chronic neurodegenerative and autoimmune disorders such as Alzheimer's disease (AD) and multiple sclerosis, supporting the concept that spreading inflammation via EVs release may play a role in these neuropathologies (Taylor and Gercel-Taylor, 2014;Xiao et al, 2017;Pieragostino et al, 2018). Thus, nSMase inhibitors have emerged as new pharmacological agents for preventing release of EVs and thus can modulate inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies indicate that myeloid cells can release EVs/MP that spread inflammatory signals both in vitro and in vivo to alter neuronal functions (Harrison-Brown et al, 2016;Nigro et al, 2016;Beneventano et al, 2017;Kumar et al, 2017). Importantly, EV levels are significantly increased following TBI in humans and animal models, as well as in chronic neurodegenerative and autoimmune disorders such as Alzheimer's disease (AD) and multiple sclerosis, supporting the concept that spreading inflammation via EVs release may play a role in these neuropathologies (Taylor and Gercel-Taylor, 2014;Xiao et al, 2017;Pieragostino et al, 2018). Thus, nSMase inhibitors have emerged as new pharmacological agents for preventing release of EVs and thus can modulate inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 94%
“…The cargo varies depending on type and differentiation of the parent cell, microenvironmental variables, and agents that triggers EV release. Cargo contents include lipid mediators (e.g., eicosanoids), proteins (e.g., cytokines, chemokines, growth factors or other mediators of signal transduction), genetic material (e.g., mRNAs, long/short noncoding RNAs, nuclear and mt DNA) and, in the case of larger vesicles, whole organelles (e.g., mitochondria) [16][17][18]. While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc.…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…Due to their substantial stability, EVs circulate systemically and have been detected in basically all body fluids, including blood, urine, cerebrospinal fluid, saliva, milk, and tears [16,[42][43][44][45][46][47][48]. Moreover, there is clear indication that EVs can cross multiple biological barriers, as demonstrated by the finding of glial/neuronal EVs in the cerebrospinal fluid, blood, tears, and urine [44].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…The secreted SMase amount measured in the supernatant after 24 h of cell culture ( Figure 2B) was most consistent with the mRNA levels of SMPD1, coding for ASM. Therefore we focused further on ASM and determined whether ASM could also be packaged into sEVs, or exosomes, similar to what was described for exosomes in the cerebrospinal fluid of multiple sclerosis patients [9]. The ASM content in the exosome enriched fraction differed from cell line to cell line.…”
Section: Patients Show a Dysregulation In Lipid Metabolism With Anmentioning
confidence: 80%
“…As Carpinteiro et al showed in a melanoma model, a higher secretion of ASM could result in the formation of ceramide-enriched membrane platforms on tumor cells, allowing integrins to cluster on these platforms and thus allowing diffuse metastasis of melanoma cells [8]. In multiple sclerosis, a higher secretion of ASM was attributed to the secretion of ASM-enriched exosomes in the cerebrospinal fluid of these patients [9]. Exosomes are a type of small extracellular vesicles (sEVs) formed inside multivesicular endosomes.…”
Section: Introductionmentioning
confidence: 91%